2022
DOI: 10.1038/s41612-022-00265-3
|View full text |Cite
|
Sign up to set email alerts
|

Addressing nitrogenous gases from croplands toward low-emission agriculture

Abstract: The use of nitrogen fertilizers in agriculture produces significant quantities of nitrogenous gases including ammonia, nitric oxide, and nitrous oxide. Through better farmland management practices, the emission of nitrogenous gases can be reduced while realizing clean water environment and climate-smart agriculture. In this article, we first provided an overview of the international movements on reducing nitrogenous gas emissions from farmlands. Then, we summarized the effect of agricultural management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 133 publications
(214 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, agriculture has the unique potential to provide a beneficial contribution to the global carbon budget. For example, agriculture produces large amounts of nitrogen, one of the long-lived greenhouse gases, due to the use of fertilizers such as nitrogen fertilizers (Northrup et al, 2021;Pan et al, 2022). To better understand food security and greenhouse gas emissions, high spatial-resolution cropland area monitoring is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, agriculture has the unique potential to provide a beneficial contribution to the global carbon budget. For example, agriculture produces large amounts of nitrogen, one of the long-lived greenhouse gases, due to the use of fertilizers such as nitrogen fertilizers (Northrup et al, 2021;Pan et al, 2022). To better understand food security and greenhouse gas emissions, high spatial-resolution cropland area monitoring is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to crop‐rotation strategies, adjusting fertilization methods and rates to better suit specific crops as well as using targeted crop species that are more efficient in nutrient use can also increase yields (Ebbisa, 2022; Guo et al., 2020; Pan et al., 2022). Improving such local to regional farmland management strategies could lead to a reduced need for fertilizers and improve both the quality of soil and water resources as well as enhancing future food production at local‐global scales (Billen et al., 2021; Chang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the causal network is to address the gap in the representation of the feedback links (dashed lines in figure 2), to identify the interrelationships among indicators and feedback mechanisms of lake eutrophication. The concept of the causal network is novel in environmental science and the system interactions of the DPSIR framework have been understudied (Lundberg 2005, Niemeijer and de Groot 2008, Svarstad et al 2008, Srebotnjak et al 2012, Gregory et al 2013, Dolbeth et al 2016, Chang et al 2022. It is demonstrated that representing the system complexity in its entirety is useful for efficient policymaking and sustainable water quality management (Smith and Schindler 2009, Friberg 2014, Scharin et al 2016, Teurlincx et al 2019a, Birk et al 2020, Huang et al 2022.…”
Section: Need To Develop a Causal Networkmentioning
confidence: 99%